2022
DOI: 10.1111/bjso.12518
|View full text |Cite
|
Sign up to set email alerts
|

Why are beliefs in different conspiracy theories positively correlated across individuals? Testing monological network versus unidimensional factor model explanations

Abstract: A substantial minority of the public express belief in conspiracy theories. A robust phenomenon in this area is that people who believe one conspiracy theory are more likely to believe in others. But the reason for this "positive manifold" The positive manifold of beliefs about conspiraciesOne robust empirical phenomenon in the literature on conspiracy theories is the observation that beliefs in different conspiracy theories tend to be positively correlated across individuals. In other words, individuals who c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…One of the most robust findings in scholarship on conspiracy beliefs is that the endorsement of specific CTs is typically highly correlated, that is, a person who endorses any one conspiracy belief is relatively more likely to also endorse any other (Bruder et al, 2013; Goertzel, 1994), even if these beliefs are logically incompatible (Imhoff & Lamberty, 2020; Wood et al, 2012). Conspiracy beliefs thus form a closely knit belief network (Williams et al, 2022) that systematically sorts people into believers of differing degrees (Frenken & Imhoff, 2021). This has led some authors to infer a latent variable behind these specific theories, a general mind-set to see the world as secretly governed by elites, a conspiracy mentality (Imhoff & Bruder, 2014).…”
Section: Differentiating General Mind-setand Specific Ctsmentioning
confidence: 99%
“…One of the most robust findings in scholarship on conspiracy beliefs is that the endorsement of specific CTs is typically highly correlated, that is, a person who endorses any one conspiracy belief is relatively more likely to also endorse any other (Bruder et al, 2013; Goertzel, 1994), even if these beliefs are logically incompatible (Imhoff & Lamberty, 2020; Wood et al, 2012). Conspiracy beliefs thus form a closely knit belief network (Williams et al, 2022) that systematically sorts people into believers of differing degrees (Frenken & Imhoff, 2021). This has led some authors to infer a latent variable behind these specific theories, a general mind-set to see the world as secretly governed by elites, a conspiracy mentality (Imhoff & Bruder, 2014).…”
Section: Differentiating General Mind-setand Specific Ctsmentioning
confidence: 99%
“…These works are in line with an alternative interpretation of the positive intercorrelation between conspiracy beliefs, namely, the self-reinforcing web of beliefs (Goertzel, 1994). In this approach, conspiracy beliefs are not interrelated because they are underpinned by a latent variable, but because they causally impact each other (Williams et al, 2022). This interpretation, which was questioned by the finding that contradictory conspiracy beliefs are positively correlated (Wood et al, 2012;Sutton & Douglas, 2014), found renewed support in network analyses (Williams et al, 2022).…”
Section: The Antecedents Of Conspiracy Mentalitymentioning
confidence: 61%
“…In this approach, conspiracy beliefs are not interrelated because they are underpinned by a latent variable, but because they causally impact each other (Williams et al, 2022). This interpretation, which was questioned by the finding that contradictory conspiracy beliefs are positively correlated (Wood et al, 2012;Sutton & Douglas, 2014), found renewed support in network analyses (Williams et al, 2022). An implication of this approach is that conspiracy mentality may sometimes be a consequence, rather than a cause, of belief in conspiracy theories.…”
Section: The Antecedents Of Conspiracy Mentalitymentioning
confidence: 99%
“…A basic finding in this research domain is that belief in one conspiracy theory positively predicts belief in another conspiracy theory (Abalakina-Paap et al, 1999; Goertzel, 1994; Swami et al, 2011). This finding has inspired the theoretical insight that people differ in their tendency to attribute events to conspiracies, which has been referred to as a conspiratorial mindset, a monological belief system, or conspiracy mentality (e.g., Imhoff & Bruder, 2014; Lewandowsky et al, 2013; Miller, 2020; Sutton & Douglas, 2014; Swami et al, 2011; Williams et al, 2022).…”
mentioning
confidence: 95%